2020
DOI: 10.3390/ijerph17082770
|View full text |Cite
|
Sign up to set email alerts
|

Business Models in Water Supply Companies—Key Implications of Trust

Abstract: Currently, trust is one of the key factors that ensures the acceptable mechanisms of economic and social relationships. It is not only an element of correct communication, but also a factor in inter-organizational bonds and a source of social dialogue. Trust has become a factor in the creation of value, as well as a key component of the conceptualization and operationalization of business models. It has revealed many problems at the strategic level, in the water sector in particular. From this perspective, tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Smitskikh et al (2020) set out a model for social entrepreneurship in the CE, taking into account the interested parties and their environmental, social and economic impacts, and defend how the determining factor in the development of CE is the long term effects of social entrepreneurship. Jabłoński and Jabłoński (2020) analyse the role of trust in the social business models in the Polish water sector, verifying how social capital registers fairly low levels in Poland and trust‐based risk holds a strong influence over the establishing of trust‐based social business models.…”
Section: Resultsmentioning
confidence: 99%
“…Smitskikh et al (2020) set out a model for social entrepreneurship in the CE, taking into account the interested parties and their environmental, social and economic impacts, and defend how the determining factor in the development of CE is the long term effects of social entrepreneurship. Jabłoński and Jabłoński (2020) analyse the role of trust in the social business models in the Polish water sector, verifying how social capital registers fairly low levels in Poland and trust‐based risk holds a strong influence over the establishing of trust‐based social business models.…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors, such enterprises work towards environmental and social sustainability in their core business activities. Jabło ński and Jabło ński [66] identified that social enterprise predominately contributes to community and society at the same time, and generates profits typically invested in the business itself. Using the example of water supply companies, the authors argued that social enterprises traditionally have holistic consideration of the impact of business activities on the environment and society while maintaining economic viability.…”
Section: Social Enterprise and Cbmmentioning
confidence: 99%
“…Environmental and social sustainability-oriented mindset and contribution were seen as the significant attributes of social enterprise identified by Staicu [65] and were also evident from Company X, which underpins the job creation of disabled young people and diverts waste from landfills and extends the product lifespan by collaborative value addition. Thus, it contributes to the community and, at the same time, generates revenue [66]. From the interview with the CEO of the social enterprise, it is seen that his motivation for solving the waste-related problem was motivated by CE principles and strategies, which play an essential role in transitioning to a CE at scale [64].…”
Section: Circular Social Entrepreneurship and Business Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and practical aspects of creating an effective business model of the enterprise in the face of intensifying competition are covered in the works og A. Afuah [2], G. Bernarda [3], A. Gambardella, A. McGahan [4], D. Debelak [5], A. Jablonski [6], H. Kupalova [7], A. Magomedova [8], J. Magretta [9], Mahmoodi, M.; Roman, M.; Prus, P. [10], A. Osterwalder, Y. Pigneur [11], M. Porter [12], Š. Slávik [13], N. Strekalova [14], P. Thomson [15], G. Kharitonova [16], H. Chesbrough [17], D. Sj ödin, V. Parida [18], C. Zott [19] and others. In the works of these scientists, scientific approaches to the essence of the business model of the enterprise are studied.…”
Section: Introductionmentioning
confidence: 99%